Vertaaloperaties in literair vertalen: het verschil tussen keuzes gemaakt door studenten en de erkende vertaler - Eszenyi, Réka (Department of Dutch and South African Studies, Faculty of English, 2013)
When translating a text, the translator always has to make choices, which determine the quality of the translated text in the end. Depending on the distance between the typology and the culture of the source language and the target language, transformations need to be performed at the level of grammar and vocabulary in order to make the translated texts comprehensible for the readers of the target language. In the case of translating from Dutch, an Indo-European language, into Hungarian, a language that belongs to the Finno-Ugric language family, it is essential that the translator is aware of the need for these transformations. The following investigation focuses on the transformations used in the Hungarian translation of a Dutch novel by an acknowledged translator, and by university students of Dutch who have just started literary translation. The results of the pilot study show that the students use much less transformations and that might deteriorate the comprehensibility of the translated text. The didactic lesson one can learn form the investigation is that in translation classes students should be sensitized to the exsistence and importance of these transformations, by analysing acknowledged translators’ and students’translations.
Keywords: literary translation; transformations; translation procedures; awarenessraising; cultural differences